An Inventory Approach to the Assessment of Main Traditional Landscapes in Sicily (Central Mediterranean Basin) - Barbera, Giuseppe; Cullotta, Sebastiano (LANDSCAPE RESEARCH, 2012)
EU policy for the conservation of cultural landscapes is of particular importance for a region such as Sicily (Italy) which is the site of many Mediterranean traditional cultural landscapes as well as new landscapes created by contemporary agriculture. Such variety of landscape, however, is not supported or confirmed by specialised inventories that identify and classify the typical Main Traditional Landscape (MTL). On the basis of these considerations, the objective of the present paper is to draw up a preliminary inventory and present a brief characterisation of MTLs in Sicily, in line with the multidisciplinary experiences and approaches implemented at European and national levels. In defining the typological units, the terminology used to identify Sicilian MTLs was modified by experiences developed on the mainland, with entries such as: bocage/semi-bocage, coltura promiscua, Mediterranean open field, mountain landscape, huerta and terrace landscape. Using different spatialised data layers, including those concerned with the main historical processes of land use and land use change, a total of eight MTLs have been detected, mapped, and concisely described. The distribution and importance of terracing systems within the different MTLs is highlighted as one of the most relevant traditional elements in the rural scenario.
From Duplicate 1 (
Keywords: agro-forestry systems; cultural landscape; ecological-cultural diversity; Land use change; landscape character

Reconstructing past cultural landscape and human impact using pollen and plant macroremains - Sadori, L.; MERCURI, A. M.; MARIOTTI LIPPI, M. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2010)
Abstract Three examples of plant landscape shaping, carried out by Iron Age populations living in different geographical areas, are presented. The examples differ in population type (Garamantes, Etruscans, and Romans), archaeological context (settlement, necropolis, furnace, port), and area of plant exploitation (respectively, Fezzan ? Libyan Sahara and Tuscany, Latium ? central Italy). The leitmotiv of the three parallel investigations highlighted that humans induced clear changes in plant cover modifying the quantitative ratio among native elements and spreading the plants of economic interest even outside of their natural habitats. Micro- and macroremain analyses once more enhanced that landscape reconstruction depends on both wild and cultivated plants, and that the cultural plant landscape is composed of a complex mixture of indigenous and exotic elements. Archaeobotany results in great help in reviewing ancient prejudices, rewriting history in a modern ecological view, also discovering a different role in the landscape evolution of past civilizations. In this light, the Garamantes deeply transformed the oases in agrarian producer sites, and the Etruscans, in the area of the Gulf of Follonica, modified the previous forest vegetation, probably enhancing the xeric features. The Romans, believed as the main creators of the environmental changes in the Mediterranean basin, surprisingly did not produce consistent plant changes in the area of the Tiber delta, in the surroundings of the imperial port of Rome, during the first century AD.
doi: 10.1080/11263504.2010.491982doi: 10.1080/11263504.2010.491982The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Archaeobotany; cultural landscape; Etruscans; Garamantes; Iron Age; macroremains; pollen; Romans